2016
DOI: 10.1002/prca.201600004
|View full text |Cite
|
Sign up to set email alerts
|

Neuroproteomic study of nitrated proteins in moderate traumatic brain injured rats treated with gamma glutamyl cysteine ethyl ester administration post injury: Insight into the role of glutathione elevation in nitrosative stress

Abstract: Purpose The aims of this study are to establish a time point to determine the most beneficial time to administer GCEE post incident to reduce oxidative damage and second, by using redox proteomics, to determine if GCEE can readily suppress 3-NT modification in TBI animals. Experimental design By using a moderate traumatic brain injury model with Wistar rats, it is hypothesized that the role of 3-nitrotyrosine (3-NT) formation as an intermediate will predict the involvement of protein nitration/nitrosation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…The intravenous injection of 100 μmol/kg (33.54 mg/kg) of GSHee elicited an array of responses in freely-moving adult male Sprague–Dawley rats and had dramatic effects on the responses elicited by subsequent injection of fentanyl (100 μmol/kg). It is likely that GSHee exerts its effects in naïve rats by increasing levels of GSH and metabolites (γ-glutamylcysteinyl and cysteine) in cells (e.g., neurons) in which GSH 53 74 and the metabolites 82 , 105 108 affect a number of biological processes. It is unlikely that GSHee directly inhibits OR function (loss of affinity or down-regulation of membrane accessible receptors) since GSHee augmented the analgesic effects of fentanyl, which are known to be OR-mediated 15 .…”
Section: Resultsmentioning
confidence: 99%
“…The intravenous injection of 100 μmol/kg (33.54 mg/kg) of GSHee elicited an array of responses in freely-moving adult male Sprague–Dawley rats and had dramatic effects on the responses elicited by subsequent injection of fentanyl (100 μmol/kg). It is likely that GSHee exerts its effects in naïve rats by increasing levels of GSH and metabolites (γ-glutamylcysteinyl and cysteine) in cells (e.g., neurons) in which GSH 53 74 and the metabolites 82 , 105 108 affect a number of biological processes. It is unlikely that GSHee directly inhibits OR function (loss of affinity or down-regulation of membrane accessible receptors) since GSHee augmented the analgesic effects of fentanyl, which are known to be OR-mediated 15 .…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that GGC may increase GSH levels in the clinic with potential as adjunct therapy for the treatment of disorders associated with acute and/or chronic GSH depletion. Previous preclinical studies have demonstrated little or no toxicity following administration of GGC (Joshi et al, 2007; Espinosa-Diez et al, 2015; Zhang et al, 2015; Ding et al, 2016; Henderson et al, 2016; Salama et al, 2016). The present study set out for the first time to evaluate GGC as a GSH-elevating strategy in primary human astrocytes, starting from homeostatic levels, with promising data.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, a prior study using a novel closed skull injury model in mice demonstrated that transcranial administration of GSH ameliorated brain injury and neuroinflammation (Roth et al, 2014). Moreover, multiple studies have shown that administration of various GSH precursors, including N-acetylcysteine and gamma-glutamylcysteine ethyl ester, as well as the GSH analog, S-nitrosoglutathione, provide antioxidant and neuroprotective effects in mouse and rat models of TBI (Xiong et al, 1999; Hicdonmez et al, 2006; Reed et al, 2009; Lok et al, 2011; Khan et al, 2009, 2011; Henderson et al, 2016). Although these studies are quite supportive of a therapeutic role for GSH in TBI, most are somewhat limited in scope in that they only evaluated neuronal degeneration and various indices of oxidative or nitrosative stress while neglecting to assess cognitive or motor deficits induced by TBI.…”
Section: Discussionmentioning
confidence: 99%